P764 Prevalence of Autoimmune diseases among first- and second-degree relatives of patients with inflammatory bowel diseases. A case–control survey in Israel. (25th January 2019) - Khoury, T; Mari, A; Mhamed, L; Mahamid, M
Abstract: Background: Inflammatory bowel diseases (IBD) include Crohn's disease (CD) and ulcerative colitis (UC) and are chronic, relapsing, inflammatory diseases of the gastrointestinal tract with an unknown aetiology. They are complex, multi-factorial disorders, in which genetic factors play a major role, the so-called phenomenon of familial aggregation or clustering of IBD. A positive family history of IBD is generally reported among CD and UC probands, with percentages varying depending on the geographic context in which the studies are carried out. Israel is a complex and pluralistic society comprising of two major ethno-national groups and, as such, represents a unique living laboratory in which to test the role of genetic factors in the development of IBD as well as of other autoimmune disorders (ADs). More in detail, in Israel there reside 1.5 million Arab individuals representing up to 20% of the total population. Jews, and in particular Ashkenazi Jews, tend to exhibit a higher risk of CD as well as of other ADs. While studies have found a lower prevalence of ADs among Arabs when compared with Jews, few studies directly compare the two ethnicities Methods: The present case–control study was designed to compare the rate of autoimmune disorders in first- and second-degree relatives of IBD patients, stratifying according to Jew and Arabic ethnicity Results: We found that first-degree relatives of Jews patients had a higher risk of developing ADs (OR 1.89 [95% CI 1.18–3.03], p = 0.0086). Classifying ADs into systemic and local (endocrinological, gastrointestinal, dermatological, and neurological), first-degree relatives of Jews patients had a higher OR of developing local ADs (OR 2.12 [95% CI 1.25–3.62], p = 0.0056). Conclusions: IBD are a complex, multi-factorial group of ADs. First-degree relatives of Israeli Jew IBD patients exhibit a statistically significant higher risk of developing ADs (in particular local ADs, such as gastrointestinal ones). General practitioners and physicians should be aware of this and explore carefully the familial pedigree when managing and treating Israeli Jew IBD patients